2020
DOI: 10.17240/aibuefd.2020..-566843
|View full text |Cite
|
Sign up to set email alerts
|

Ortaokul Ve Li̇se Öğrenci̇leri̇ni̇n İnternet Bağimliliği Düzeyleri̇ İle Akademi̇k Başarilari Ve Bazi Deği̇şkenlerle İli̇şki̇leri̇ni̇n İncelenmesi̇ - İzmi̇r Bayrakli Örneği̇

Abstract: Bu çalışmada, İzmir-Bayraklı İlçesinde dört lise ve sekiz ortaokulda 1118 öğrenci ile yapılan çalışmada, öğrencilerde internet bağımlılığı oranları ve bazı değişkenler ile akademik başarıları arasındaki ilişkileri belirlenmeye çalışılmıştır. Araştırmada,"Young İnternet Bağımlılığı Ölçeği"nin kısa formu kullanılmış, kişisel bilgiler ve akademik başarı formu araştırmacı tarafından hazırlanmıştır. Elde edilen verilerin istatistiksel analizi ve değerlendirilmesi sonucunda, ortaokul ve lise öğrencilerinin %1,4 'ünü… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…It is very thought-provoking that university students want to use social media on the other platform instead of working academically. Internet use in studies of young people, which has become increasingly widespread, is not for homework, research or learning, but it has been shown that they use it for communication purposes and social media purposes (Demirel, Yörük, & Özkan, 2012;Mertoğlu, 2020;Yang, Lu, Wang, & Zhao, 2014;Yılmaz, Şahin, Haseski, & Erol, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…It is very thought-provoking that university students want to use social media on the other platform instead of working academically. Internet use in studies of young people, which has become increasingly widespread, is not for homework, research or learning, but it has been shown that they use it for communication purposes and social media purposes (Demirel, Yörük, & Özkan, 2012;Mertoğlu, 2020;Yang, Lu, Wang, & Zhao, 2014;Yılmaz, Şahin, Haseski, & Erol, 2014).…”
Section: Discussionmentioning
confidence: 99%